Tinjauan Sosiologi Pendidikan Mengenai Aksi Vandalisme Pelajar - Irma Inesia Sri Utami; Regina Febriani; Shofia Saniah Nuriah; Putri Khoirunnisa (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
This research was conducted to determine the form of vandalism and to analyze the factors that caused vandalism at MTs Arrofiiyah. This research applies a qualitative approach that focuses on case studies. The research participants consisted of 21 students aged between 15 and 16 years who conducted resource interviews and collected primary data based on the results of field studies. School facilities in the form of chairs, tables, doors, walls and so on are targets for students to carry out acts of vandalism. The form of this act of vandalism is play vandalism, which is the factor that causes vandalism to occur because of empty hours which make students feel bored and want to play around. Efforts made by the school to prevent acts of vandalism are by providing scoring or sanctions to every perpetrator of vandalism. The school is also trying to improve supervision and provide constructive alternative activities to fill students' free time. Regarding acts of vandalism, this shows that play vandalism often occurs without planning and is carried out impulsively by students. This indicates that the lack of structured activities can trigger negative behavior among students. Thus, it is important for schools to design programs that can attract student interest and reduce opportunities for vandalism